The Influence of Ludo Edutainment Media in the Prevention of Child Sexual Abuse at Pao-Pao Elementary School, Gowa Regency - Aswadi; Sukfitrianty Syahrir; Roza Qoni Hadza (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Child sexual abuse is one of the most serious public health issues faced by children across all cultures and societies. Several studies have shown that edutainment is an effective strategy to influence awareness, knowledge, attitudes, and behaviors related to health. Assessing the impact of Edutainment media Ludo in the prevention of sexual abuse of children at Pao-Pao Elementary School, Gowa Regency. Method: The research method used is experimental research with a pre-experimental design. The study is based on primary data obtained directly through pre-test and post-test questionnaires, and secondary data obtained from case reports from the South Sulawesi Regional Police, LPA (Child Protection Agency), as well as data from P2TP2A (Integrated Service Center for Women and Children Victims of Violence). Result: The results of statistical analysis show that there is a difference in knowledge before and after the intervention related to sexual abuse of children, with a p-value < 0.05 (0.002). There is a difference in attitudes before and after the Edutainment media Ludo intervention, with a t-value of 5.447 and a p-value of 0.000 < 0.05. There is also a difference in children's skills before and after the Edutainment media Ludo intervention, with a t-value of 2.561 and a p-value of 0.000 < 0.05. Conclusion: There is an effect of local-language Edutainment media on children's knowledge, attitudes, and skills towards the prevention of sexual violence against children at Pao-Pao Elementary School, Gowa Regency.